2020
DOI: 10.1002/eng2.12258
|View full text |Cite
|
Sign up to set email alerts
|

A complex garment assembly line balancing using simulation‐based optimization

Abstract: The nascent wave of disruptive competition in the current business environment brought about by the fourth industrial revolution (Fashion 4.0 or Apparel 4.0) is enormous. Therefore, it is important for the apparel industry to be flexible enough to respond quickly to the unstable customers' demand through continuous improvement of their process efficiency and productivity. This study proposed assembly line balancing problem (ALBP) for complex garment assembly line using simulation-based optimization under stoch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 68 publications
0
8
0
Order By: Relevance
“…This is because it reduces both cycle time and WIP. In spite of the fact that the metamodel was not used for model prediction, the present study found it most suitable for inference [30], and for initial solution (local optimal) for optimization process [52]. The inference was drawn from the linear regression metamodel to analyze the factors' effects on throughput.…”
Section: Plos Onementioning
confidence: 90%
“…This is because it reduces both cycle time and WIP. In spite of the fact that the metamodel was not used for model prediction, the present study found it most suitable for inference [30], and for initial solution (local optimal) for optimization process [52]. The inference was drawn from the linear regression metamodel to analyze the factors' effects on throughput.…”
Section: Plos Onementioning
confidence: 90%
“…Therefore, simulation-based optimization techniques are widely used to evaluate the optimization problems of complex manufacturing systems. Bongomin et al [31] applied Arena software to develop the discrete event simulation of the assembly line, and both local and global optimization methods have significantly improved the production efficiency of the assembly line.…”
Section: Related Studiesmentioning
confidence: 99%
“…Moreover, the optimization approaches can be integrated to simulation techniques which is called simulation-based optimization approaches. These approaches have been adopted to manufacturing systems' optimization, efficiently [46]. For example, [47] developed a simulation-based optimization approach using a discrete event simulation model and simulated annealing (SA) algorithm, to solve a production planning and resource allocation problem in reconfigurable manufacturing system.…”
Section: Optimization Approaches For Assembly Line Balancingmentioning
confidence: 99%